(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2020)
The present study is based on a special project modality, which had the objective to develop an instructional material about the sound and fundamental elements in electroacoustics. The material was developed through a multimedia resource based on HTML5, a tool for the construction of virtual environments, as a didactic strategy in the teaching of the Musical Informatics subject, taking as objects of study the students of the second semester of the Degree in Music of the Universidad Centroccidental Lisnadro Alvarado. The main trends of this type of resources based on Information and Communication Technologies (ICT) are presented. A diagnosis of need was made, with a research instrument, which was validated by expert judgment. The programs that were used in the elaboration and application were studied, which corresponded to the modality of free software that were available to the students and we proceeded to study the topics related to sound, authors, composers and electroacoustic instruments, as well as opensource of software that allows the creation, editing and mastering of audio.